2012
DOI: 10.1088/0264-9381/29/24/245015
|View full text |Cite
|
Sign up to set email alerts
|

Local thermal equilibrium and KMS states in curved spacetime

Abstract: On the example of a free massless and conformally coupled scalar field, it is argued that in quantum field theory in curved spacetimes with time-like Killing field, the corresponding KMS states (generalized Gibbs ensembles) at parameter β > 0 need not possess a definite temperature in the sense of the zeroth law. In fact, these states, although passive in the sense of the second law, are not always in local thermal equilibrium (LTE). A criterion characterizing LTE states with sharp local temperature is discuss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Specifically, if one treats a scalar field model with the conformal coupling to gravity, then one can find that Φ 2 (x) = T 2 /12 in a thermal state characterized by the temperature T . This was also generalized and treated in curved spacetimes [10][11][12][13]. Certain applications in flat space were studied in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, if one treats a scalar field model with the conformal coupling to gravity, then one can find that Φ 2 (x) = T 2 /12 in a thermal state characterized by the temperature T . This was also generalized and treated in curved spacetimes [10][11][12][13]. Certain applications in flat space were studied in [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we showed that it can be isometrically mapped to a state on the past horizons, as expressed in equation (40). This result shows how expectation values of observables in the region M are related to the expectation values on the horizons.…”
Section: Discussionmentioning
confidence: 56%
“…The authors of [28] went even further and proved the nonexistence by showing that such a state would give rise to contradictions related to causality. We remark that the point of view adopted in [28] is more robust because, recently, a novel definition of local thermal equilibrium has been proposed [8,9] and one of the consequences of this definition is that a thermal state does not always describe a situation in which local thermal equilibrium is attained [10,40]. We do not wish to extend the discussion here, but we will address this topic in more detail in a future work.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting interactions is a massive field accompanied by a massless field. The important observation here is that the charge of the conserved symmetry current, whose charge before the field shift was related to a finite global charge 49 Different from spinor QED which only has one coupling parameter, the renormalization of a pointlike scalar gauge coupling leads in addition to a quadrilinear selfcoupling of the matter field.…”
Section: Zero Mass Limits and A Perturbative Scenario For Confinementmentioning
confidence: 88%
“…As a result of the two derivatives, the two-pointfunctions on the left hand side involves fields of scaling dimension 2. The resulting scaling degree 4 of the 2-pointfunction leads to a delta function renormalization counterterm in T LL | 1−contr with undetermoned coefficient c. Our main interest is the fulfillment of the relations (49) in the tree approximation. It is clear that the use of the T 0 1-contraction contribution will not fulfill (49).…”
Section: Scalar Massive Qedmentioning
confidence: 99%